Os sentidos de língua portuguesa no vestibular da FUVEST - Santos Júnior, Gilberto Egydio dos (Universidade Federal de São Carlos, 2011)
The present work entitled "The meaning of the Portuguese language in the college entrance exam FUVEST" intends to analyse the designation of the Portuguese language by means of a semantical study. FUVEST was created in 1976/77 under a linguistic paradigm, adopting a linguistic variation approach in opposition to the traditional grammar test. Based on the test statements as a corpus, it will be discussed how meanings are created between standard language and its variations. Thus it will be possible to notice how the Portuguese language has been having its meaning established in Brazil´s main college entrance exam.
Keywords: Língua portuguesa; Acontecimento; Fundação Universitária para o Vestibular; Semântica; Político; Gramática; Língua de cabide; FUVEST; Event; Political; Grammar; Semantics; Language hanger; LINGUISTICA, LETRAS E ARTES::LINGUISTICA